1986
DOI: 10.1002/1098-2337(1986)12:4<237::aid-ab2480120402>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Instigating and measuring interpersonal aggression and hostility: A methodological contribution

Abstract: Two experiments were conducted, employing a 2 × 2 factorial design, to assess both 1)a relatively controlled procedure for instigating aggressive inclinations and 2) a way of measuring interpersonal aggression that is much more subtle than most of the laboratory procedures now being used. In both of these experiments half of the subjects were provoked by exposing them to a self‐esteem‐threatening evaluation ostensibly from a peer. After this “treatment,” in experiment 1 all of the subjects had an opportunity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Emotional susceptibility is defined as a stable tendency to feel distressed, inadequate, and vulnerable to perceived threats (Caprara, 1982;Caprara et al, 1983;Caprara, Renzi, et al, 1986). Caprara (1982) hypothesized that emotional susceptibility reflects a propensity to experience negative affect and a tendency to become upset and defensive when confronted with personal attacks and insults.…”
Section: Emotional Susceptibilitymentioning
confidence: 99%
“…Emotional susceptibility is defined as a stable tendency to feel distressed, inadequate, and vulnerable to perceived threats (Caprara, 1982;Caprara et al, 1983;Caprara, Renzi, et al, 1986). Caprara (1982) hypothesized that emotional susceptibility reflects a propensity to experience negative affect and a tendency to become upset and defensive when confronted with personal attacks and insults.…”
Section: Emotional Susceptibilitymentioning
confidence: 99%
“…Although provocation may take many forms, ranging from minor frustrations to physical attacks, it is often verbal. Verbal provocation may in turn be overt, as in blatant personal insults, or can be veiled, as in disparagement humor (e.g., Caprara, Passerini, Pastorelli, Renzi, & Zelli, 1986; Janes & Olson, 2000; Zillmann, 1983). Yet, all hitherto studied forms of verbal provocation involve a communicator delivering an unpleasant message to and about others (“observers”).…”
mentioning
confidence: 99%
“…Although much of the research on the frustration–aggression hypothesis has occurred within the realm of video game competition/violence (Williams & Clippinger, 2002), it is argued that the basic premise of the frustration–aggression hypothesis may well inform the current design. Furthermore, Caprara, Passerini, Pastorelli, Renzi, and Zelli (1986) suggested that more subtle forms of aggression align more closely with participants’ negative ratings of a confederate following an insult than aggressive responding. Participants may also be more likely to exhibit subtle forms of aggression in the laboratory because these behaviors may be more socially acceptable, but still offer important information about aggressive intentions (Caprara et al, 1986).…”
Section: Emotion Regulation Development and Aggression In Menmentioning
confidence: 99%
“…Furthermore, Caprara, Passerini, Pastorelli, Renzi, and Zelli (1986) suggested that more subtle forms of aggression align more closely with participants’ negative ratings of a confederate following an insult than aggressive responding. Participants may also be more likely to exhibit subtle forms of aggression in the laboratory because these behaviors may be more socially acceptable, but still offer important information about aggressive intentions (Caprara et al, 1986). Therefore, measuring changes in competitive intent toward and attributions about a target when that target has instigated negative emotion by thwarting goal-directed behavior (i.e., criticizing his performance during a social task) may represent a subtle form of aggression.…”
Section: Emotion Regulation Development and Aggression In Menmentioning
confidence: 99%